2017
DOI: 10.1108/sbm-03-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Institutional isomorphism and social responsibility in professional sports

Abstract: Purpose The purpose of this paper is to explore the corporate social responsibility (CSR) practices of three major professional sport leagues in South Korea to investigate the general beliefs, values, and norms influencing the institutional isomorphism of CSR engagement. Design/methodology/approach Nine semi-structured interviews were conducted with three league chiefs of CSR initiatives and senior managers of related divisions to explore the general beliefs, values, and norms that are institutionalized in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
7
0
3
Order By: Relevance
“…culture) defines the rule of the game in society (Baddache & Nicolai, 2013;Schultz & Wehmeier, 2010). Thus, companies that are in the same institutional environment have homogeneous forms of behaviour to get legitimacy (Ilhan-Nas, Koparan, & Okan, 2015;Joo, Larkin, & Walker, 2017;Lauesen, 2014), including making sustainability report. This is what we call as isomorphism.…”
mentioning
confidence: 99%
“…culture) defines the rule of the game in society (Baddache & Nicolai, 2013;Schultz & Wehmeier, 2010). Thus, companies that are in the same institutional environment have homogeneous forms of behaviour to get legitimacy (Ilhan-Nas, Koparan, & Okan, 2015;Joo, Larkin, & Walker, 2017;Lauesen, 2014), including making sustainability report. This is what we call as isomorphism.…”
mentioning
confidence: 99%
“…By the end of July 2020, there had been no update on the resumption of the W-League. These differences in NFAs movement through response phases are indicative of the institutional environments and point towards the social and cultural value structures that are present (Joo et al, 2017). This study is the first to outline pandemic response phases of sports organisations and highlights the importance of communication through the first two phases of alteration and decision-making.…”
Section: Doimentioning
confidence: 85%
“…Isomorphism could be imposed by coercive means, mimetic processes or simply by normative matters (Powell, 2016). In South Korea for example, it was shown that social responsibility was part of the isomorphism clubs experienced (Joo, et al, 2017), and although initially social responsibility was perceived as a cost, in the long run it had a positive impact in the clubs overall image.…”
Section: Institutionalization and Legitimacy In Sportsmentioning
confidence: 99%